Calibration parameters for the passive sampling of organic UV filters by silicone; diffusion coefficients and silicone–water partition coefficients. (May 2019) - Verhagen, Rory; O'Malley, Elissa; Smedes, Foppe; Mueller, Jochen F.; Kaserzon, Sarit
Abstract: In recent years, organic ultraviolet filters (UVFs) received considerable attention as a group of emerging contaminants, including in Australia where the use of UVFs is particularly relevant. Passive sampling using polymers has become widely used for routine monitoring of chemicals in the aquatic environment. Application of passive samplers for monitoring chemicals in the water relies on calibration data such as chemical's polymer-water partition coefficient ( K pw ) and diffusion coefficients in the sampling material ( D p ), for understanding uptake and kinetic limitations. In the present study, K pw and D p for nine UVFs were estimated. K pw values were determined in different water – polymer partition experiments where (1) a given mass of chemicals was dosed into the water and (2) into the polymer. Diffusion coefficients were determined using the stacking method. The estimated log K pw and log D p ranged from 2.9 to 6.4 L kg −1 and -11.1 to −10.5 m 2 s -1, respectively. The sufficient high D p allows application of kinetic models that only consider water boundary-controlled uptake for converting silicone sampler uptake into an aqueous phase concentration using the presented K pw . Graphical abstract: Image 1 Highlights: Nine polymer-water partition coefficients of UV-filters are reported. Nine diffusion coefficients of these UV-filters are reported. Three UV filter partition & diffusion coefficients are reported for the first time. The Single dose design is adequate to estimate the partition coefficients.